Can Meaning Make Cents? Making the Meaning of Work Salient for US Manufacturing Workers - Alberto Salamone; Grace Lordan (Institute of Labor Economics (IZA), 2022)
We conducted a field experiment in a small electronics manufacturing firm in the US with the specific aim to improve minutes worked, punctuality, tardiness and safety checks. Our intervention was to put posters on the production floor on a random day, which made salient to the blue-collar employees the meaning and importance of their job, which comprised of routine repetitive tasks, in a before and after design. Overall, the intervention was a success with positive and significant effects consistently found for the outcomes both immediately after the experiment finished (+3 days) and also more than two weeks after (+15 days). Our study highlights it is possible to motivate blue collar manual workers intrinsically by drawing attention to the meaning of their work.
Keywords: J10; 330; meaning; motivation; blue collar; manufacturing; field experiment